Three dimensional ultra‐high‐density electro‐anatomical cardiac mapping in horses: methodology. (19th February 2020) - Van Steenkiste, Glenn; De Clercq, Dominique; Boussy, Tim; Vera, Lisse; Schauvliege, Stijn; Decloedt, Annelies; van Loon, Gunther
Abstract: Background: Ultra‐high‐density cardiac mapping allows very accurate characterisation of atrial and ventricular electrophysiology and activation timing. Objective: To describe the technique and evaluate the feasibility of magnetic electro‐anatomical mapping of the equine heart. Study design: In vivo experimental method development. Methods: A mapping system using an 8.5F bidirectional deflectable catheter with a deployable mini‐basket (3–22 mm) containing 64 electrodes divided over eight splines was evaluated. Based upon predefined beat acceptance criteria, the system automatically acquires endocardial electrograms and catheter location information. Electro‐anatomical maps were acquired from four horses in sinus rhythm under general anaesthesia. Results: All endocardial areas within each chamber could be reached. Access to the left atrium required the use of a deflectable sheath. With the exception of the left atrial map of horse 1, all four chambers in all four horses could be mapped. Optimisation of the beat acceptance criteria led to a reduction in manual correction of the automatically accepted beats from 13.1% in the first horse to 0.4% of the beats in the last horse. Main limitations: Only a limited number of horses were included in the study. Conclusion: Ultra‐high‐density 3D electro‐anatomical mapping is feasible in adult horses and is a promising tool for electrophysiological research and characterisation of complex arrhythmias.